Relationship between neuropsychiatric symptoms and cognitive impairment in Parkinson's disease / Michelle Chan Su Ann - Michelle , Chan Su Ann (2017)
Patients with Parkinson’s Disease (PD) experience not only motor but also non-motor symptoms (NMSs). Neuropsychiatric symptoms (NPS) and cognitive impairment which are part of the NMSs, are prevalent among PD patients. Although NPS are more prevalent in those with PD dementia, the association is unclear. At present, there is no data describing the associations between NPS and cognitive impairment in Malaysia. Objective: The main objective of this study is to investigate the association between NPS and cognitive impairment in PD patients. We also explored the neuropsychiatric profile in our sample population. Method: This is an observational, hospital-based, cross-sectional study on 94 patients with PD. Patient Demographic Questionnaire was used to record socio-demographic and clinical data. NPS were assessed using the Neuropsychiatric Inventory (NPI) and the cognitive impairment with Neuropsychiatry Cognitive Assessment Tool (NUCOG). The Hoehn and Yahr scale were used to assess the stage of Parkinson disease (Stages 1 to 5) particularly in the motor function. The Mann Whitney test was performed to investigate the association between socio-demographic/clinical factors and NPS to cognitive impairment. The Chi-Square test was performed to analyze if any one NPS significantly changes a subject’s odds of having advanced cognitive deficits. Linear regression was vii performed to compare the relative importance of the selected significant NPS with NUCOG scores with corrections for the bias from socio-demographic and clinical factors. Results: The mean age was 64.89 years old (SD= 9.34). Most subjects received up to secondary education (56.4%) and 23.4 % received tertiary education. The mean duration of PD was 9.70 years (SD: 5.89). 12.7 % had advance staged PD. Subjects with advanced PD (p<0.01), requiring assistance in their functioning (p<0.001) and on Benzodiazepines (p<0.01) had significantly higher NPI scores. PD subjects fared worse in all cognitive domains of NUCOG with the mean score of 73.7% (SD: 19.34). The only significant factor found to be significantly associated with NUCOG score was education level (p<0.01). Subjects with tertiary education scored significantly higher in all cognitive domains except for executive function. Subjects with advanced PD (p<0.001), who required any form of assistance (p<0.001) and who were on anti-dementia (p<0.05) scored significantly lower in the total NUCOG and all domain scores. Subjects with delusion (p<0.01), hallucinations (p<0.05), agitation/ aggression (p<0.05), irritability (p<0.05) and sleep disturbances (p<0.05) showed overall cognitive impairment. Hallucinations (p<0.05), delusions (p<0.05) and irritability (p<0.05) are particularly associated with NUCOG score <80. However, after correcting for education, hallucination was the only symptom that achieved a significant negative correlation with NUCOG scores (p<0.05). Conclusion: Subjects performed poorly in all 5 cognitive domains of NUCOG: language, memory, executive function, visuo-constructional and attention. This study shows an association between hallucination and cognitive impairment.